Removal of total nitrogen from wastewater by a combination of Chlorella sp. and audible sound - Thanh-Luu Pham (IWA Publishing, 2021)
In developing countries, nitrogen in the traditional market wastewater is a critical environmental problem. In this study, the microalga Chlorella sp., which was isolated from wastewater, was used to remove the total nitrogen (TN) from conventional market wastewater in combination with audible sound (Vietnamese classical music). In addition, effects of sound exposure on removal efficiency at different initial cell densities were analyzed. Results revealed that music sound control demonstrates potential to improve the removal efficiency. TN removal efficiencies of 96%, 69.5%, and 4.3% were observed for treatments with Chlorella sp./audible sound, Chlorella sp., and without Chlorella sp., respectively. The significance of probability value (p-value) (<0.05) on the paired sample t-test confirmed the critical role of audible sound and Chlorella sp. density on the TN removal in screening experiments. The predicted optimal conditions for TN removal were as follows: a Chlorella sp. density of 4%, an audible sound of 52.5 dB, and a cultivation time of 4.6 days. Results based on statistical analysis revealed that the quadratic models for TN removal are significant at a low p-value (<0.05) and a high predicted coefficient of determination (R2 = 0.9452) value. The obtained statistical results also indicated that most of the variables are significant for the abatement of TN from market wastewater using Chlorella sp. HIGHLIGHTS Chlorella sp. with audible sound employed to remove total nitrogen (TN) from traditional market wastewater.; The central composite design had been developed on three factors on TN removal.; ANOVA showed a well fitted polynomial regression model with R2 of 0.9908.; The statistical results indicate audible sound has a significant effect on TN removal.; The TN removal was reached 98.12% at optimum condition.;